Health and Education Expenditures in Russia, the Baltic States, and the Other Countries of the Former Soviet Union - Horton, Mark. (Washington, D.C. : International Monetary Fund, 1996)
Russia, the Baltic states and the other countries of the former Soviet Union inherited health and education systems that were in need of substantial structural and financial reform. In spite of a sharp decline of real resources, this reform has barely begun. While health and education have not suffered disproportionate cuts, employment has been maintained, with real wages sharply compressed, purchases of materials reduced and energy-related spending taking a greater share of resources in many countries. Structural and financial reform would include reducing staffing and physical capacity, while increasing expenditures for materials and wages for the more highly qualified.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet